Optimal Placement of multiple Distributed Generators using a Novel Voltage Stability Indicator employing Arithmetic Optimization Algorithm - Khan M.T.; Singh P.; Chauhan A.; Arya R.; Verma A.; Titare L.S.; Choube S.C. (My University, 2025)
With the extensive application of renewable energy operated distributed generation plants in the power system, certain issues need to be addressed. One such problem is the optimal location of these DG units, as their random placement may result in congestion in certain paths of the transmission network. This paper proposed a novel voltage stability indicator (VSI) that is incorporated in the objective function along with real power loss reduction and minimum voltage deviation. The prominent feature of this VSI is the utilization of phasor data available through Phasor Measurement Units (PMUs) in the recent power systems. This VSI performs satisfactorily for both mesh and radial networks. The developed method under the paper is tested on IEEE-30 bus network. To optimize the objective function, Arithmetic Optimization Algorithm (AOA) is used and the obtained results have been compared with Particle swarm optimization. Simulation results justified the applicability of this technique for reducing losses in the network. © 2023